2011
DOI: 10.1128/cvi.00304-10
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of a Multicomponent Meningococcal Serogroup B Vaccine and a Quadrivalent Meningococcal CRM 197 Conjugate Vaccine against Serogroups A, C, W-135, and Y in Adults Who Are at Increased Risk for Occupational Exposure to Meningococcal Isolates

Abstract: Laboratory staff who work with meningococcal isolates are at increased risk for developing invasive disease relative to the general population. This was the first study of laboratory workers who received both a conjugate vaccine against meningococcal serogroups A, C, W-135, and Y (Men ACWY-CRM, Menveo) and an investigational multicomponent vaccine against serogroup B containing factor H binding protein, neisserial adhesin A, Neisseria heparin binding antigen, and New Zealand strain outer membrane vesicles (4CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 16 publications
6
76
0
1
Order By: Relevance
“…[19][20][21][22] Results from Phase 2 and 3 clinical studies demonstrated that 4CMenB elicited strong bactericidal responses against the vaccine antigens and was generally well tolerated when used in infants and children, adolescents and adults. [21][22][23][24][25][26] 4CMenB has been approved in the EU, Australia, Canada, Chile, and Uruguay for use in individuals beginning from 2 months of age and in the US for use in individuals 10 to 25 y of age.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Results from Phase 2 and 3 clinical studies demonstrated that 4CMenB elicited strong bactericidal responses against the vaccine antigens and was generally well tolerated when used in infants and children, adolescents and adults. [21][22][23][24][25][26] 4CMenB has been approved in the EU, Australia, Canada, Chile, and Uruguay for use in individuals beginning from 2 months of age and in the US for use in individuals 10 to 25 y of age.…”
Section: Introductionmentioning
confidence: 99%
“…Though there was no statistically significant difference in SBA responses between the two vaccines, a logarithmic regression looked at the effect of the concentration of human factor H on immunogenicity and found that at high fH concentrations, the mutant vaccine generated slightly higher bactericidal responses. Nonetheless, humans vaccinated with wild-type fHBP generate substantial SBA titers (77)(78)(79)(80)(81)(82)(83), demonstrating that this is not a relevant concern for human vaccines. Recently, another meningococcal surface protein, NspA, was found to bind to human fH and contribute to bacterial complement resistance for some MnB strains (45).…”
Section: Evidence That Human Factor H Is the Ligand For Fhbpmentioning
confidence: 99%
“…Sequential administration of 4CMenB and Menveo Âź provided robust evidence of an immune response against all serogroups. Both vaccines were well tolerated [97]. The percentage of infants with hSBA titers of 1:4 or higher against reference strains were 100, 98 and 93% after the booster dose [93] 5CVMB (rMenB) + OMV strain NZ98/254…”
Section: Reverse Vaccinology and Universal Vaccine For Serogroup B Menimentioning
confidence: 99%